Kaposi Sarcoma in Hand: Case Report - Karakurt, Lokman; Köse, Rüştü (Fırat University, 2003)
Occurrence of Kaposi sarcoma in hand is rare. Classical Kaposi sarcoma is a tumour of senile patients in Mediterranean countries. Males are more frequently affected from this tumour. Its clinical progress is very slow and patients often die from other causes. A 75 years old female patient was admitted with a purple lesion on the dorsal of hand, this painless lesion was started of about two months ago. Excision was performed for diagnose and treatment. It was pathologically diagnosed as caposi sarcoma. At the second month of the follow up period a new lesion was appeared on the dorsal side of the same hand. She was referred to a further health centre for radioterapy. No recurrence occurred in 16-month follow up after second excision in this health centre. Surgical intervention might have better results in small and single Kaposi sarcoma lesion.

Kaposi sarkomunun el tutulumu nadirdir. Klasik Kaposi sarkomu Akdeniz ülkelerindeki yaşlı hastaların tümörüdür. Erkekler çok daha sık etkilenmektedirler. Klinik seyri yavaş olup, hastalar genelde araya giren başka sorunlardan ölebilirler. 75 yaşında bayan hasta, sağ el dorsal yüzde iki ay önce başlayan, mor renkte ağrısız bir lezyonla başvurdu. Hastaya tanı ve tedavi amacı ile eksizyon yapıldı. Patolojik tanı Kaposi sarkomu idi. Takibinin ikinci ayında aynı elin dorsal yüzünün başka yerinde yeni bir lezyon oluştu. Radyoterapi için hasta ileri bir merkeze sevk edildi. Burada eksizyon tedavisi uygulanan hastanın 16 aylık takibinde ikinci nüks görülmedi. Kaposi sarkomunun küçük ve tek lezyonlarının tedavisinde cerrahi eksizyonla da başarılı sonuçlar alınabilmektedir.
Elin Kaposi Sarkomu: Olgu Sunumu